REKAYASA PENGURAIAN KEPADATAN LALU LINTAS PADA SIMPANG TANPA SINYAL (STUDI KASUS: JALAN URIP SUMOHARJO, JALAN GUNUNG BAWAKARAENG, JALAN MASJID RAYA DAN JALAN MACCINI BARU) - Gilbert, Juan; Mursalim; Kalangi, Hendry Tanoto (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Atma Jaya Makassar, 2025)
Traffic density at junctions without signal often causes congestion and lowers the performance of the transportation network. This research aims to design intersections so that the length of vehicle queues can be reduced. The case study was conducted at the intersection of Urip Sumoharjo Street, Gunung Bawakaraeng Street, Masjid Raya Street and Maccini Baru Street. This type of research is a case study using methods namely quantitative. The research was carried out with direct observation in the field to collect geometric data of intersections, traffic volume, and traffic speed. The results of the analysis show that the use of vissim software can help design the reduction of traffic density at intersections without signal. It was found that the high traffic density, especially at peak hours in the afternoon (using the gas station entrance) is Queue Counter 1 (Masjid Raya Street-Urip Sumoharjo Street) along as 167m and in Queue Counter 2 (Masjid Raya Street-Gunung Bawakaraeng Street) along as 262m. Research results show that changing the road type from 4/2 D to 6/2 D can reduce the length of the vehicle queue. By using the Queue Counter feature in Vissim Software, Queue Counter 1 (Masjid Raya Street-Urip Sumoharjo Street) is 108m and Queue Counter 2 (Jalan Masjid Raya-Jalan Gunung Bawakaraeng) is 182m. This solution can help analyse traffic density and improve the performance of the transportation network in the area.